Role of bestatin as a treatment for periodontitis - Rama Varma, Sudhir; Elagha, Bader Mohamed Moustafa; Narayanan, Jayaraj K.; Mathew, Asok (Frontiers in Dental Medicine, 2025)
Periodontitis is a chronic inflammatory disease impacting the supporting structures of teeth, with significant global pervasiveness and systemic health implications. Current treatments, such as scaling and root planning (SRP) and adjunctive antibiotics, face challenges including antibiotic resistance, infection recurrence, and incomplete tissue regeneration. Bestatin, a dipeptide aminopeptidase inhibitor, has shown potential as a novel therapeutic agent due to its targeted antimicrobial effects against Porphyromonas gingivalis (P. gingivalis), biofilm modulation, and anti-inflammatory properties. in vitro studies revealed bestatin's selective bacteriostatic effects against P. gingivalis, inhibiting bacterial growth and biofilm development without affecting commensal bacteria. in vivo studies demonstrated that bestatin modulated inflammatory responses and prevented necrotic abscess formation in guinea pig models, suggesting its potential to suppress P. gingivalis growth through alternative pathways. However, no clinical trials were identified, highlighting a significant gap in the translation of preclinical findings into human periodontal therapy. The current review highlights Bestatin as a promising therapeutic representative for periodontitis, where it is involved in inhibiting modulating biofilms, reducing tissue destruction, and P. gingivalis, in preclinical studies. Compared to traditional therapies, bestatin provides unique advantages, non-cytotoxicity, including specificity, and dual action against microbial dysbiosis along with biofilm-associated resistance.